Core Courses in Public Health Laboratory Science and Practice: Findings from 2006 and 2011 Surveys. (September 2013) - Deboy, John M.; Beck, Angela J.; Boulton, Matthew L.; Kim, Deborah H.; Wichman, Michael D.; Luedtke, Patrick F.
Objectives: We identified academic training courses or topics most important to the careers of U.S. public health, environmental, and agricultural laboratory (PHEAL) scientist-managers and directors, and determined what portions of the national PHEAL workforce completed these courses. Methods: We conducted electronic national surveys in 2006 and 2011, and analyzed data using numerical ranking, Chi-square tests comparing rates, and Spearman's formula measuring rank correlation. Results: In 2006, 40 of 50 PHEAL directors identified 56 course topics as either important, useful, or not needed for someone in their position. These course topics were then ranked to provide a list of 31 core courses. In 2011, 1, 659 of approximately 5, 555 PHEAL scientific and technical staff, using a subset of 25 core courses, evidenced higher core course completion rates associated with higher-level job classification, advanced academic degree, and age. The 2011 survey showed that 287 PHEAL scientist-managers and directors, on average, completed 37.7% ( n =5/13) of leadership/managerial core courses and 51.7% ( n =6/12) of scientific core courses. For 1, 659 laboratorians in all scientific and technical classifications, core-subject completion rates were higher in local laboratories (42.8%, n =11/25) than in state (36.0%, n =9/25), federal (34.4%, n =9/25), and university (31.2%, n =8/25) laboratories. Conclusions: There is a definable range of scientific, leadership, and managerial core courses needed by PHEAL scientist-managers and directors to function effectively in their positions. Potential PHEAL scientist-managers and directors need greater and continuing access to these courses, and academic and practice entities supporting development of this workforce should adopt curricula and core competencies aligned with these course topics.